THE INFLUENCE OF SERVANT LEADERSHIP AND TALENT MANAGEMENT ON THE PERFORMANCE OF TEACHERS OF YOGYAKARTA 2nd FORCE MOVEMENT SCHOOL TEACHERS WITH EMPLOYEE ENGAGEMENT AS AN INTERVENING VARIABLE - Nurdiah, Siti; Dwi Hery Yulianto (LPPM Akademi Manajemen Administrasi Yogyakarta, 2024)
This study aims to examine the impact of servant leadership and talent management on teacher performance within the 2nd generation cohort of driving schools in Yogyakarta City, with employee engagement serving as an intermediary variable. Data for this research was gathered using a questionnaire. The sampling method employed was a census, targeting a population of 45 teachers from the Yogyakarta City 2nd generation driving school group. Hypothesis testing was conducted through linear regression analysis for hypotheses 1 through 5, and path analysis and the Sobel test for hypotheses 6 and 7, utilizing the SPSS 27 for Windows software. The findings indicate that at a 5% significance level: (1) Servant leadership does not significantly affect employee engagement; (2) Talent management significantly influences employee engagement; (3) Servant leadership significantly impacts teacher performance; (4) Talent management significantly impacts teacher performance; (5) Employee engagement does not significantly affect teacher performance; (6) Employee engagement does not significantly mediate the relationship between servant leadership and teacher performance; (7) Employee engagement does not significantly mediate the relationship between talent management and teacher performance.